2020
DOI: 10.24200/sci.2020.53355.3198
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of glutathione in hemolysed erythrocytes

Abstract: The physiological significance of determining glutathione (GSH) and its oxide form is obvious from their applications in clinical practices such as diagnostic experiments for diabetes, Parkinson's disease, and cancers. Such an important detemination still needs the development of certain experimental procedures that are easy, fast, and cheap enough to implement. These procedural advantages can be provided through electrochemical methods. Therefore, in this study, at the surface of a glassy carbon electrode (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The detection limit and linear range of GSH and GSSG are 1.2, 1.1 nM, and 2.3-1197.4, 2.4-1248.3nM, respectively. The analytical parameters of some other electrochemical sensing or biosensing devices for GSH [128][129][130][131][132][133][134][135][136][137][138][139][140] are listed in Table 4 (see more comprehensive list in Table S4 in SI).…”
Section: Glutathione (Reduced Gsh/ Oxidized Gssg)mentioning
confidence: 99%
“…The detection limit and linear range of GSH and GSSG are 1.2, 1.1 nM, and 2.3-1197.4, 2.4-1248.3nM, respectively. The analytical parameters of some other electrochemical sensing or biosensing devices for GSH [128][129][130][131][132][133][134][135][136][137][138][139][140] are listed in Table 4 (see more comprehensive list in Table S4 in SI).…”
Section: Glutathione (Reduced Gsh/ Oxidized Gssg)mentioning
confidence: 99%
“…The physicochemical properties of Metoclopramide Analytical methods previously published for the quantification of metoclopramide in bulk [13,14,15], pharmaceutical dosage forms [16,17,18], and biological fluids were scanned in the literatüre [19,20,21]. Spectrophotometric [22,23,24], high-performance liquid chromatographic [25,26,27], and liquid chromatographic coupled with tandem mass spectrometry (LC-MS/MS) [28] methods were reported for determination of metoclopramide in pharmaceutical dosage forms and biological fluids were developed.…”
Section: Tablementioning
confidence: 99%
“…A survey of the literature reported that metoclopramide hydrochloride was estimated under optimal conditions by different spectrophotometric methods and using various chemical reagents, such as: azo-dye coupling (3)(4)(5)(6)(7)(8)(9)(10)(11), oxidative coupling (12)(13)(14), Schiff base Reaction (15), and charge transfer complex (16). A number of researchers were able to estimate (MCP.H) by using other spectrophotometric methods such as UV, colored ion-pair complex, oxidation, reduction reaction and nucleophilic substitution reaction, in the presence of chemical reagents and under various optimal condition (17)(18)(19)(20), diverse HPLC methods (21)(22)(23)(24)(25), FIuorescent analysis (26), and Glassy carbon electrode (GCE) were also used (27). Currently, the recent methodological development in analytical chemistry gave rise to a plethora of improved and durable versions of an environmentally friendly approach (28), some of these concepts are safe compounds (29).…”
Section: Introductionmentioning
confidence: 99%